49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-950
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Pressure Characterization of a Wind Tunnel Force Balance using the Single Vector System

Abstract: Wind tunnel research at NASA Langley Research Center's 31-inch Mach 10 hypersonic facility utilized a 5-component force balance, which provided a pressurized flow-thru capability to the test article. The goal of the research was to determine the interaction effects between the free-stream flow and the exit flow from the reaction control system on the Mars Science Laboratory aeroshell during planetary entry. In the wind tunnel, the balance was exposed to aerodynamic forces and moments, steady-state and transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The analysis of the split plot design was accomplished using JMP software [11]. A complete discussion of the analysis of a second-order split-plot design using JMP software is provided by Lynn et al [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the split plot design was accomplished using JMP software [11]. A complete discussion of the analysis of a second-order split-plot design using JMP software is provided by Lynn et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…The stand-alone constant temperature MBBD would be repeated at each of three temperatures. If time allowed, the MBBD could be replicated at each temperature for a fully crossed design, which allows for ordinary least-squares equivalence and pure error analysis [4,[6][7][8][9]. Limited resources led to the choice of replicated centers.…”
Section: Split-plot Crossed Designmentioning
confidence: 99%
“…Such apparent strain was quantified using a function relevant to the magnitudes of the temperature as applied to the testing environment, although the origin of this strain was not clarified. In the measurements of forces and moments in wind tunnel tests using strain gauge balances, the influences on the measurements by the thermal gradients in the balances were evidenced [13][14][15]. The overall output of these strain gauge balances was shown to be reversible when the temperature in the balances was recovered.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the balance with low temperature sensitivity produced smaller errors in the measured forces and moments as a result of temperature changes in the balance during a wind tunnel test. For the elimination the thermal and pressure effects, Lynn et al 7 developed a statistically designed experiment to characterize the behavior of the balance over the expected wind tunnel operating temperatures. Due to the strain gage measurement theory, the balance should be designed as a thin-walled structure so that the balance is liable to deformation by external force.…”
Section: Introductionmentioning
confidence: 99%